Management of Major Depressive Disorder by Citalopram: A Double-edged Sword - Abbas, Kashif; Alam, Mudassir; Akhtar, Md. Tanwir; Hussain, Raghib; Mustafa, Mohd; Usmani, Nazura; Habib, Safia (Current Psychiatry Research and Reviews, 2025)
Major depressive disorder (MDD) affects over 280 million people globally, presenting a significant public health challenge. This review evaluates the use of citalopram, a selective serotonin reuptake inhibitor (SSRI), in MDD management, focusing on its therapeutic efficacy and the critical adverse effect of citalopram-induced hyponatremia (CIH). Through a comprehensive literature analysis, we explore the medicinal chemistry of citalopram, its mode of action, and the mechanisms underlying CIH, primarily associated with the syndrome of inappropriate antidiuretic hormone secretion (SIADH). Findings indicate that CIH affects 9-40% of patients, with a higher prevalence in vulnerable populations such as the elderly and cancer patients, where it complicates treatment due to interactions with disease-related factors. Routine serum sodium monitoring is recommended for individuals at risk to mitigate potential risks. The review highlights the need for tailored treatment strategies to balance citalopram’s benefits against CIH risks, particularly in cancer patients, and identifies future research directions for personalized MDD management.
Keywords: SIADH